Analisis Makna Gender dalam Perspektif Al-Qur’an - Akmal Alna; Faizah Binti Awad; Nurdin; Muh. Ikhsan; Fatira Wahidah (Gunung Djati Conference Series, 2022)
This study aims to examine gender in the perspective of the Qur'an and how to understand the differences between gender and sex. This research uses library research method. The primary sources in writing this article include references that discuss implicitly or explicitly about gender. The references obtained are then edited, coded, reduced, verified and analyzed, to be further studied further in order to find the right understanding related to gender. The results of this research and discussion show that gender and sex are different in terms of meaning and function and must be understood with the right understanding. This study concludes that the verses of the Qur'an that discuss gender always emphasize both parties without any tendency or affection for one gender.